Is it possible to revive dug wells in hard-rock India through recharge?: discussion from studies in ten districts of the country - Krishnan, S.; Indu, R.; Shah, Tushaar; Hittalamani, C.; Patwari, B.; Sharma, D.; Chauhan, L.; Kher, V.; Raj, H.; Mahida, U.; Shankar, M.; Sharma, K. (2009)
Groundwater exploitation in hard-rock India is leading to high distress amongst farmers. Various water conservation schemes have been tried and piloted, but no idea has scaled up to the national level. An idea of revitalizing groundwater use, individual as it is, and if still individual-based, could possibly succeed. Recharging through dug wells is one such thought. After mass movements in Saurashtra in the mid-1990s, no effort has been made to promote the idea nationally, till now. The current national program on artificial recharge of dug wells hopes to do so. But this idea can succeed only if farmers see any value in it and try to make it successful. A survey of 767 farmers owning dug wells in 10 districts of India shows that there is immense potential in, yet constraints to, dug-well recharge. A comparison of dug-well recharge with the average annual natural recharge over hard-rock areas of 116 mm shows that there is almost an equal potential in recharging groundwater irrigated areas through dug wells. Surveyed farmers also expect a great increase in water availability, especially during the dry seasons. However, farmers are wary of this recharged water flowing across to their neighbors. They expect to gain around 30% from their recharged water, but agree that there would be a common gain by recharging groundwater together with their neighbors. The farmers? estimated cost of Rs 10,000 for the recharge structures is not such a big constraint, nor is siltation, for which they suggest numerous innovative solutions. Managing dug-well recharge locally is critical. Should it become mandatory for farmers to apply in groups of 10, as our sampled farmers suggest? Should the national program be structured such that farmers are transferred the subsidy and they can construct the structures in April or May as they unanimously prefer to do? Instead, should the policy be to promote local businesses around recharge, so as to harness the experience of well drillers, who also operate during the same summer months? More such tuning is needed over implementation of the dug-well recharge program to create demand from farmers, catalyze enterprises locally around recharge and establish monitoring programs to measure the benefits from the first upcoming season in 2009 over lakhs of recharge structures.